2009
DOI: 10.1115/1.3005169
|View full text |Cite
|
Sign up to set email alerts
|

Material Properties of the Axillary Pouch of the Glenohumeral Capsule: Is Isotropic Material Symmetry Appropriate?

Abstract: Inconclusive findings regarding the collagen fiber architecture and the material properties of the glenohumeral capsule make it unclear whether the material symmetry of the glenohumeral capsule is isotropic or anisotropic. The overall objective of this work was to use a combined experimental and computational protocol to characterize the mechanical properties of the axillary pouch of the glenohumeral capsule and to determine the appropriate material symmetry. Two perpendicular tensile and finite simple shear d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…A combined experimental–computational approach was utilized to determine the material coefficients for the glenohumeral capsule based on an isotropic constitutive model 12,16,32,37. Tissue samples were excised from each capsular region shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A combined experimental–computational approach was utilized to determine the material coefficients for the glenohumeral capsule based on an isotropic constitutive model 12,16,32,37. Tissue samples were excised from each capsular region shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The length, width, and thickness of the tissue sample were prescribed and the experimentally recorded elongation was used to drive the simulations. An inverse finite element optimization routine determined the material coefficients for an isotropic hypoelastic constitutive model that has been used previously to model the glenohumeral capsule 16,37,39,45. Since two sets of coefficients were determined for the axillary pouch and posterior regions, the average of the material coefficients served as input to the finite element models (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…28 Following recovery, the capsule was positioned in the reference strain configuration and re-inflated to 0.75 psi. The positions of the strain markers were recorded and served as the non-recoverable strain state.…”
Section: Methodsmentioning
confidence: 99%
“…A recent experimental study on the subfailure mechanical properties of the glenohumeral axillary pouch found its biaxial properties were not significantly different. 20 The current study suggests that isotropy may be found in failure properties as well.…”
Section: Discussionmentioning
confidence: 86%
“…25 Failure criteria for ligamentous materials are not sufficiently developed at this time to predict the role of the minimum principal strain on failure. 4,9,10,28 While glenohumeral capsule is membranous in nature, few studies to date have tested its biaxial mechanical properties, 15,20 likely because such testing is difficult. Numerous studies have excised thickened portions of the capsule such as the IGHL in BoneLigament-Bone specimens (BLB) and then subjected them to uniaxial tests.…”
Section: Introductionmentioning
confidence: 99%